Effect of boron-nitrogen modified soybean oil additive on biodegradability, anti-oxidation property, and lubricity of rapeseed oil. (February 2020) - Liu, Ping; Wang, Xin; Wu, Jiang; Lin, Wang; Feng, Yanhan; Chen, Boshui; Fang, Jianhua; Jiang, Zeqi
Two novel boron-nitrogen modified soybean oil additives with different length of chain structures (abbreviated as BNS1 and BNS2) were synthesized. The thermal stability of BNS1 and BNS2 was evaluated by thermo-gravimetric analysis. The effect of the as-synthesized additives on the biodegradability, anti-oxidation property, and lubricity in rapeseed oil was evaluated by respective standard method. Moreover, the morphology and tribochemical characteristics of the worn surfaces were examined by scanning electron microscope assembled with energy dispersive spectrometer. The results indicated that BNS1 and BNS2 both possess good thermal stability; BNS1 slightly impairs the biodegradability of rapeseed oil, but BNS2 facilitates the biodegradability of rapeseed oil. BNS1 and BNS2 could improve the anti-wear and friction-reducing performance of the rapeseed oil, but BNS1 exhibited better anti-wear ability as compared to that of BNS2, BNS2 exhibited better anti-wear ability in reducing friction coefficients as compared to that of BNS1. The enhanced anti-wear and friction-reducing abilities of rapeseed oil were ascribed to the formation of a composite boundary lubrication film due to the strong adsorption of BNS1 or BNS2 and rapeseed oil onto the lubricated surfaces and their tribochemical reactions with metal surfaces. BNS1 and BNS2 could both facilitate the anti-oxidation properties of the rapeseed oil.